Disabled athletes` classifications as Paralympic sports progress factor - Abalyan, A. G.; Evseeva, O. E.; Evseev, S. P.; Kirillov, A. V. (Theory and Practice of Physical Culture, 2018)
Objective of the study was to analyze the key progress avenues for the Paralympic sport disciplines in the context of different classifications of Paralympians based on analyses of the available literature on the subject and Paralympians` classification reports of the International Paralympic Committee, Russian Paralympic Committee and International Sport Federations. The Federations generally apply the classifications by the relevant diagnoses including cerebral palsy (?P-ISRA); amputees and orthopaedic conditions (ISOD); blind and vision impaired athletes (IBSA); spinal cord injuries (ISMGF); people with intellectual disabilities (INAS); and adaptive sports classifications applied by the Russian sport federations. On the whole, the modern classifications are dominated by the following three ones: medical/ general classification; sport functionality classification; and handicap rating classification. New classifications may be viewed among the key factors of influence on the global modern Paralympic sports on the whole and specific Paralympic sport disciplines in particular.